2000
DOI: 10.1016/s0022-5347(05)67995-5
|View full text |Cite
|
Sign up to set email alerts
|

The Optimal Systematic Prostate Biopsy Scheme Should Include 8 Rather Than 6 Biopsies: Results of a Prospective Clinical Trial

Abstract: The 6 systematic biopsies of the peripheral zone are inadequate and a minimum of 8, including the apex, mid lobar mid gland, lateral mid gland and lateral base, should routinely be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
219
1
22

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 430 publications
(248 citation statements)
references
References 10 publications
6
219
1
22
Order By: Relevance
“…For the 493 men who underwent biopsy, this equates to a 6% increase in the rate of cancer detection from 27% (sextant only, 133/493) to 33% (extended biopsies, 164/493). This ®nding is in general agreement with other published extended biopsy protocols [7,21,22]. Although the present sampling technique may have differed from those in other reports, it is clear that prostate cancer detection can be signi®cantly improved by taking more biopsies (within reason) and sampling regions of the prostate not incorporated in the routine sextant protocol.…”
Section: Discussionsupporting
confidence: 90%
“…For the 493 men who underwent biopsy, this equates to a 6% increase in the rate of cancer detection from 27% (sextant only, 133/493) to 33% (extended biopsies, 164/493). This ®nding is in general agreement with other published extended biopsy protocols [7,21,22]. Although the present sampling technique may have differed from those in other reports, it is clear that prostate cancer detection can be signi®cantly improved by taking more biopsies (within reason) and sampling regions of the prostate not incorporated in the routine sextant protocol.…”
Section: Discussionsupporting
confidence: 90%
“…2,15 In contrast, minor complications are frequent, with 60-79%. 5,16 Most of these complications do not require any intervention and are selflimiting. However, it is essential to have a clear understanding of the true morbidity of this procedure to counsel the patient accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…In the face of low morbidity, the TRUS-PB is performed as an outpatient procedure. 2,[5][6][7] Although the incidence of major complications associated with TRUS-BP is low, minor complications such as urinary tract infection, dysuria, hematuria and hemospermia are frequent. 2,6 Although many studies have reported the incidence of complications, they were not specifically designed to evaluate the true complication rate and its implications.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies found that extended biopsy schemes result in an increased detection rate for prostate carcinoma and, specifically, that biopsy locations outside of the standard sextant location are more likely to be positive. 17,18 Therefore, we examined data separately for men who underwent sextant biopsies and men who had Ͼ 6 cores obtained. We found that the ability of the percentage of cores positive from the dominant side to predict PSA failure was similar, whether it was examined among men who underwent sextant biopsy or men who underwent an extended biopsy scheme, and was superior to the total percentage of cores for both subsets.…”
Section: Discussionmentioning
confidence: 99%